Manajemen Strategi Pengembangan Pesantren Pasca Covid-19 di Aceh (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
The purpose of this study was to study the methods used by pesantren to promote organizational sustainability after Covid-19. The research method used is qualitative, using a descriptive survey methodology. The presentation of data is carried out by comparative analysis. The results showed that theimplementation of strategic management is oriented towards sustainability; pesantren that have successfully survived are trying to revitalize with the objectives of academic programs; the transformation of the learning system from a traditional model to technology-based learning; and the functionalization of pesantren as a facilitator of disease prevention. The social consequences of this study include an objective and reasonable evaluation from the community that pesantren have a stable and durable organizational structure. Thus, in the face of similar obstacles, pesantren can guarantee the quality of their teaching to the local community.